2017
DOI: 10.1016/j.sjpain.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

How do medical students use and understand pain rating scales?

Abstract: AbstractBackground and aimsPain is a multidimensional experience that is difficult to describe and to assess. To scale current pain, assessment refers to a maximum level of pain, but little is known about this process. Further, clinicians tend to underestimate patients’ pain, with or without patients’ own reports, and to underestimate to a greater extent with more clinical experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Thus, they require a more difficult assessment strategy, which possibly makes the students less likely to indicate them. It is in line with the observation of Zalmay and Williams [20] who determined how medical students used and understood pain rating scales. They showed that, although medical students’ recognition of the importance of facial expression was encouraging, they expected a narrow range of other pain-associated behaviors.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, they require a more difficult assessment strategy, which possibly makes the students less likely to indicate them. It is in line with the observation of Zalmay and Williams [20] who determined how medical students used and understood pain rating scales. They showed that, although medical students’ recognition of the importance of facial expression was encouraging, they expected a narrow range of other pain-associated behaviors.…”
Section: Discussionsupporting
confidence: 87%
“… 33 , 34 , 47 , 49 These findings contrast with those studies using samples from western countries, which tend to find higher preference rates for the NRS over the VRS (although several of these studies did not compare these 2 scales with the FPS or FPS-R). 15 , 31 , 38 , 48 …”
Section: Discussionmentioning
confidence: 99%